2019
DOI: 10.3847/2041-8213/ab14f1
|View full text |Cite
|
Sign up to set email alerts
|

First Measurement of the Hubble Constant from a Dark Standard Siren using the Dark Energy Survey Galaxies and the LIGO/Virgo Binary–Black-hole Merger GW170814

Abstract: We present a multi-messenger measurement of the Hubble constant H 0 using the binary–black-hole merger GW170814 as a standard siren, combined with a photometric redshift catalog from the Dark Energy Survey (DES). The luminosity distance is obtained from the gravitational wave signal detected by the Laser Interferometer Gravitational-Wave Observatory (LIGO)/Virgo Collaboration (LVC) on 2017 August 14, and the redshift information is provided by the DES Year 3 data. Black hole mergers such as G… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
165
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(169 citation statements)
references
References 70 publications
4
165
0
Order By: Relevance
“…We have not considered the use of so-called dark standard sirens, due to binary black hole (BBH) mergers that have no EM counterpart to provide a redshift. These signals can still be used for cosmography either by probabilistically identifying a well-localized source with a host galaxy in a galaxy redshift catalog [36] or by using some prior knowledge about the source population redshift distribution [37]. On an individual basis, BBH standard sirens are not as precise as systems with an EM counterpart, and so, for the time being, we have concentrated on BNS and MBHB sirens.…”
Section: Detectionmentioning
confidence: 99%
“…We have not considered the use of so-called dark standard sirens, due to binary black hole (BBH) mergers that have no EM counterpart to provide a redshift. These signals can still be used for cosmography either by probabilistically identifying a well-localized source with a host galaxy in a galaxy redshift catalog [36] or by using some prior knowledge about the source population redshift distribution [37]. On an individual basis, BBH standard sirens are not as precise as systems with an EM counterpart, and so, for the time being, we have concentrated on BNS and MBHB sirens.…”
Section: Detectionmentioning
confidence: 99%
“…As discussed by Suyu et al (2012), multiple paths to independent determinations of the Hubble constant are needed in order to assess and control systematic uncertainties (see also, Chen & Ratra 2011;Abbott et al 2017;Soares-Santos et al 2019;Freedman et al 2019). Accurate estimates of H 0 provide critical independent constraints on dark energy, spatial curvature, neutrino physics, and general relativity (Freedman & Madore 2010;Suyu et al 2012;Weinberg et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In Del Pozzo [2012] it was shown that it will be possible to determinethe Hubble-Lemaître constant with a precision of few % after 50 dark sirens detections, i.e., GW events without the concurrent presence of electromagnetic transient, see Figure 20. In a region of 10 degrees squared, say, ∼ 10 4 galaxies are expected to be present within a distance up to ∼ 500 Mpc, and even if galaxy catalogs can encompass most of the stellar mass present in the localized region, and photometric redshift determinations are available (see Soares-Santos et al [2019] for an implementation of the idea with a recent binary black hole detection), the number of candidate galaxies will induce a large error in the final measurement which be counteracted only by combining large numbers of dark sirens.…”
Section: Gravitational Wave Surveysmentioning
confidence: 99%